Visualisasi Algoritma Kruskal dan Prim dalam Mencari Rute Terpendek Berbasis Unity 3D - William Chrisnando Ekasaputra; Magdalena A. Ineke Pakereng (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Kruskal and Prim algorithms are two Minimum Spanning Tree search algorithms on a graph that has similarities. With the speedy development of technology, a new learning media emerged, namely games. This research was conducted to design and test a game that can explain and visualize how Kruskal and Prim's algorithm works. The result of this research is expected to prove the efficiency of learning Kruskal and Prim algorithm easier and at better efficiency than traditional way of studying. The data in this research originated from a questionnaire distributed to game users who are still students or students. The results showed an increasing number of game users who understood the Kruskal and Prim algorithms.